Single nucleotide polymorphisms in Plasmodium falciparum V type H(+) pyrophosphatase gene (pfvp2) and their associations with pfcrt and pfmdr1 polymorphisms. - Jovel, I; Ferreira, P; Veiga, M; Malmberg, M; Mårtensson, A; Kaneko, A; Zakeri, S; Murillo, C; Nosten, F; Björkman, A; Ursing, J (2014)
BACKGROUND: Chloroquine resistance in Plasmodium falciparum malaria has been associated with pfcrt 76T (chloroquine resistance transporter gene) and pfmdr1 86Y (multidrug resistance gene 1) alleles. Pfcrt 76T enables transport of protonated chloroquine out of the parasites digestive vacuole resulting in a loss of hydrogen ions (H(+)). V type H(+) pyrophosphatase (PfVP2) is thought to pump H(+) into the digestive vacuole. This study aimed to describe the geographic distribution of single nucleotide polymorphisms in pfvp2 and their possible associations with pfcrt and pfmdr1 polymorphisms. METHODS: Blood samples from 384 patients collected (1981-2009) in Honduras (n=35), Colombia (n=50), Liberia (n=50), Guinea Bissau (n=50), Tanzania (n=50), Iran (n=50), Thailand (n=49) and Vanuatu (n=50) were analysed. The pfcrt 72-76 haplotype, pfmdr1 copy numbers, pfmdr1 N86Y and pfvp2 V405I, K582R and P711S alleles were identified using PCR based methods. RESULTS: Pfvp2 was amplified in 344 samples. The pfvp2 allele proportions were V405 (97%), 405I (3%), K582 (99%), 582R (1%), P711 (97%) and 711S (3%). The number of patients with any of pfvp2 405I, 582R and/or 711S were as follows: Honduras (2/30), Colombia (0/46), Liberia (7/48), Guinea-Bissau (4/50), Tanzania (3/48), Iran (3/50), Thailand (1/49) and Vanuatu (0/31). The alleles were most common in Liberia (P=0.01) and Liberia+Guinea-Bissau (P=0.01). The VKP haplotype was found in 189/194 (97%) and 131/145 (90%) samples harbouring pfcrt 76T and pfcrt K76 respectively (P=0.007). CONCLUSIONS: The VKP haplotype was dominant. Most pfvp2 405I, 582R and 711S SNPs were seen where CQ resistance was not highly prevalent at the time of blood sampling possibly due to greater genetic variation prior to the bottle neck event of spreading CQ resistance. The association between the pfvp2 VKP haplotype and pfcrt 76T, which may indicate that pfvp2 is involved in CQ resistance, should therefore be interpreted with caution.